COMPREHENSIVE GERIATRIC CARE: THE “TREATMENT TRIANGLE” MODEL - Dinh Thanh, Le (Journal of Health and Aging, 2025)
As Vietnam’s population ages rapidly, the health system faces increasing demands for long-term, integrated, and person-centered care for older adults. To meet these challenges, the “Treatment Triangle” model has been proposed, comprising three interconnected pillars: (1) home and community-based care, (2) hospitalbased specialized treatment, and (3) rehabilitative and nursing care at dedicated centers. Together, these pillars form a continuum of care that emphasizes prevention, early detection, comprehensive management of chronic diseases, and recovery of physical and psychological function. This paper describes the structure, roles, and interconnections of each component and discusses how this model could serve as a sustainable and humane framework for geriatric care in Vietnam.